Vitiligo: Epidemiology and Economic Impact - Naldi, Luigi; Pagani, Adriano; Alduini, Chiara (Dermatology Practical & Conceptual, 2023)
Introduction: Vitiligo is an acquired disorder of pigmentation, characterized by the development of white patches on the skin, often with a typical symmetrical distribution and progressive extension [1,2]. Although vitiligo does not cause direct physical impairment, it can produce a relevant psychosocial burden. Despite this burden, effective treatments are lacking, emphasizing the need for new therapeutic options.Objectives: The aim of this study was to systematically scan the scientific literature for studies dealing with vitiligo epidemiology. Additionally, the study aimed to assess the social costs of vitiligo, ultimately raising awareness about the societal impact of the condition. The focus was on Italian data.Methods: Our research employed a comprehensive methodology. For the epidemiology, we systematically searched PubMed database up to October 2023 and complemented the analysis with Real World Evidence. For social costs, we conducted an in-depth literature review, administered a web-survey to 20 Italian dermatologists and conducted an equivalent number of interviews during the same period in March 2022.Results: The data suggest that in Italy the prevalence of vitiligo increases with age, and it varies from 0.19% (age 18-21) to 0.6% (age >45) [3,4]. We estimated 152,000 patients diagnosed with Non-Segmental Vitiligo (NSV) in Italy; based on Body Surface Area (BSA), 33% are Not Severe, 31% Mild, 27% Moderate/Severe, 9% Very Severe. The yearly social costs of vitiligo amount to €0.5Bln.Conclusions: There is a remarkable association of vitiligo with anxiety and depression [5,6,7,8,9], and Mental Health is associated with 30% of social costs. Moreover, vitiligo social costs distribution highlights inequity, with patients bearing 55% of them.